awareness about personal protective equipments and health problems among poultry workers (Northern International Medical College Journal, 2015)
Background: Taking protective equipment is important for poultry workers as they are at risk of poultry hazard. Use of personal protective equipment (PPE) is essential for preventing & controlling diseases experienced by poultry processing workers.Aims and Objectives: To assess the awareness about personal protective equipments and health problems among poultry workers.Method and materials: Descriptive cross-sectional study was conducted under the guidance of the Department of Community Medicine, National Institute of Preventive and Social Medicine (NIPSOM), Dhaka, from March to June 2006 on 100 poultry workers who were selected purposively from six poultry farms from the area of Gazipur districts. Informed consent was obtained and structured questionnaire was used to collect data through face to face interview. Data was edited, processed and analyzed both manually and used of SPSS version 10.Result: Mean age was 27.49% with SD ± 9.84 years, highest age range 59% was 20-30 years. Regarding level of education & economic status revealed that 43% were illiterate and 72% earned 2000-3000 taka monthly. 20% had highest work experience of 6-8 years. 82% of the respondents thought that personal protection is necessary during working in poultry. 79% of the respondents knew the name of PPE. But only 42% use PPE and 58% of the respondents did not use it. Among the user 16% use PPE regularly and 26% use PPE irregularly. Result showed significant association between education and knowledge of diseases of transmission (p